Comparing successful aging, resilience, and holistic wellness as predictors of the good life. Issue 7 (3rd July 2018) - Fullen, Matthew C.; Richardson, Virginia E.; Granello, Darcy Haag
ABSTRACT: Objectives : The purpose of the study was to compare the relative contributions of Rowe and Kahn's definition of successful aging (SA), resilience, and the holistic wellness paradigm for predicting happiness, life satisfaction, and self-rated physical health in late life. Method : A cross-sectional research design was used to survey 200 residents across 12 senior housing sites. Criteria with strong psychometric properties representing the three constructs were operationalized using hierarchical regression within the context of relevant control variables to compare the relative strengths of the three paradigms for predicting measures of quality of life. Results : In this study, 8.5% of the sample met modified criteria for SA and were used as a comparison group with those who did not meet the criteria. Overall, holistic wellness and resilience predicted happiness, life satisfaction, and physical health better than SA alone. When predicting happiness and life satisfaction, race and holistic wellness were significant predictors. Age and holistic wellness were the best predictors of self-rated physical health. Conclusion : The criteria underlying SA poorly predicted happiness, life satisfaction, and self-rated physical health compared to the resilience and holistic wellness models. The results suggest that definitions of aging well are complex and require greater nuance. The findings have important implications for clinicians seeking translatable theoretical models that are amenable to practice with older adults, especially for those living in independent senior housing communities.